Postural phenotype assessment in pupils: a new clinic approach - Nascimento, Luana Karina de Almeida; Miranda, Cristiano Barreto de; Filho, Flávio Martins do Nascimento; Cerqueira, Felipe Lima de; Araújo, Maria das Graças Rodrigues de; Júnior, Miburge Bolívar Gois (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Most of the postural problems originate during puberty, when the body structure is in the process of development and the hormonal release predisposes the differentiated growth between the gender, which can interfere in the posture and balance of the individual. Objective: To analyze the postural phenotypic parameters in school adolescents. Method: A cross-sectional study was carried out in 72 adolescents with age between 10 and 15 years from a public school in the city of Lagarto, Sergipe. The subjects were divided into two groups according to gender (G1: female group; G2: male group) and age subgroups (SB1: adolescents with 10-12 years; SB2: adolescents with 13-15 years), homogeneous in relation to BMI. The research consisted of the collection of anthropometric and clinical data, backpack weighing, static postural evaluation through biophotogrammetry and measurement of stabilometric parameters through a force platform. Results: The individuals presented reduced mobility of the spine and did not overload the school backpack. The prevalence of scoliosis and scoliotic attitudes was 33.32% and more frequentily in the G2. As for the postural angles, the G1 presented knee valgus, hyperextension of the knee and lumbar hyperlordosis, differently, the G2 was characterized with forward inclination of the body, knee flexion, cervical hyperlordosis and thoracic hyperkyphosis. There was no difference in body balance variables between gender, besides the correlation between postural alignment and balance. Conclusion: The study suggests that the phase of corporal development in the school period favors postural phenotypic differentiations.